(untitled) (JURNAL ADMINISTRASI PUBLIK, 2016)
Abstract :Raskin is a government program that purpose to reduce the burden of spending Objective Households Own Benefit (RTS-PM) through a partial fulfillment of basic needs in the form of rice. However, implementation of the policy has not worked as expected due to several factors between like low quality of rice delivered, in fact objective’s receiver of subsidized rice is not only the poor but the society who belong to afford. The purpose of this study was to determine how the distribution policy implementation Raskin in the village Poopoh Tombariri Subdistrict Minahasa district. To realize these purpose, Conducting research using descriptive qualitative approach. The data resources consist of primary data result from observation and interviews, and secondary data result from the management of documents, archives, records, and regulations related to issues in research. The results showed that the rice’s distribution policy implementation of poor society in the Poopoh Village Tombariri Subdistrict Minahasa District has not accomplished appropriate with the purpose and objectives because implementing no transparency in the distribution of rice’s raskin. Raskin distribution policy implementation refer to indicator of 6 success exact is not achieve. Keywords: Implementation Policy Rice Distribution for Poor Society